2011
DOI: 10.4238/2011.december.8.6
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to lipopolysaccharide-induced endotoxic shock in heterozygous Zfp191 gene-knockout mice

Abstract: ABSTRACT. Zinc finger protein 191, ZNF24 and Zfp191 in both humans and mice belong to the SCAN domain subfamily of Krüppel-like zinc finger transcription factors. Previous studies have suggested that Zfp191 is a pleiotropic factor involved in embryonic development, hematopoiesis and tumorigenesis. However, little is known about its target genes or its role in other physiological and pathological processes. We have identified the putative target genes of Zfp191, using an in silico genome-wide scan. Three hundre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…For instance, deficiency of zDC in classic dendritic cells presented a higher inflammatory response to LPS (14). ZFP191 gene knockout mice were resistant to LPS-induced endotoxic shock (15). Recently, several studies with deficient mice of Gfi1, a C2H2 type transcription repressor, supported it as a negative regulator in immune response and inflammation (16 -18).…”
mentioning
confidence: 99%
“…For instance, deficiency of zDC in classic dendritic cells presented a higher inflammatory response to LPS (14). ZFP191 gene knockout mice were resistant to LPS-induced endotoxic shock (15). Recently, several studies with deficient mice of Gfi1, a C2H2 type transcription repressor, supported it as a negative regulator in immune response and inflammation (16 -18).…”
mentioning
confidence: 99%
“…To further investigate this relationship, we examined the effect of ZNF24 on pro-inflammatory cytokines. A study from Fei et al [ 48 ] has reported that knockdown of the mouse zinc finger protein Zfp 191 could reduce inflammatory cytokine levels during LPS stimulation. Similarly, we found that ZNF24 knockdown attenuated the upregulation of IL-6 and IL-1β induced by TNF-α treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Oral mucositis caused by anticancer treatments was documented and evaluated according to the National Cancer Institute Common Terminology Criteria for Adverse Events 3.0 version (CTCAE 3.0) [ 48 ] weekly from the beginning of radiotherapy to one month after completion of treatment. The highest grade of oral mucositis that patients experienced during follow-up was recorded as their common toxicity criteria (CTC) scores.…”
Section: Methodsmentioning
confidence: 99%
“…Besides development, ZNF24 also participates in inflammation process. According to the data published by Sun et al,18 ZFP191(±) mice secreted less interleukin-1β and interleukin-6 upon lipopolysaccharide stimulation, thus resist to lipopolysaccharide-induced systemic inflammation and endotoxic shock. In addition, ZNF24 can promote cell migration of microvascular endothelial cells.…”
mentioning
confidence: 96%